2017
DOI: 10.1007/s00586-017-5097-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective serial MRI study following acute traumatic cervical spinal cord injury

Abstract: Purpose In acute traumatic cervical spinal cord injury (SCI) patients, we sought to characterize how objective MRI measures of injury change during the first 3 week post-injury. Methods Six MRI scans each were planned in 19 cervical SCI patients within the first 3 week post-injury. Length of cord edema, maximum spinal cord compression, maximum canal compromise, and presence and length of hematoma were measured. Results Length of spinal cord edema increased in the first 48 h after SCI, followed by a gradual dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…An inherent limitation of retrospective studies is that researchers are limited to data available for analyses, and for this study, the earliest imaging available averaged 3.7 ± 2.8 weeks. This is a possible confounder, as SCI imaging characteristics are dynamic, especially within the first 3 weeks of injury [26]. Although only one blinded researcher performed the measures in this study (which is a limitation), we are confident in the results as evidenced by reported high levels of inter-rater reliability with the same measures [11].…”
Section: Limitationsmentioning
confidence: 80%
“…An inherent limitation of retrospective studies is that researchers are limited to data available for analyses, and for this study, the earliest imaging available averaged 3.7 ± 2.8 weeks. This is a possible confounder, as SCI imaging characteristics are dynamic, especially within the first 3 weeks of injury [26]. Although only one blinded researcher performed the measures in this study (which is a limitation), we are confident in the results as evidenced by reported high levels of inter-rater reliability with the same measures [11].…”
Section: Limitationsmentioning
confidence: 80%
“…In severe injuries, the edema and hematoma can appear and increase in the first 48 hours and decrease gradually in the next three weeks, while hematoma indicates that Asia grade in the patient is A, or B, or some patients with C grade [ 23 ]. Grade A and B and neurodegenerative disorders at admission affect the prognosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies with specific subgroups of patients are needed to settle the role of early decompression both for complete and incomplete SCI. [50][51][52] The same group performed a metanalysis using as surgical timing within 24 hours and they failed to demonstrate a better outcome related to time of surgery. However, they only included patients with thoracic and thoracolumbar injury and this represents a bias of this study due to the lower incidence of trauma at this level with respect to cervical SCI and the fact that at lumbar level the injury affects less quality of life for those patients.…”
Section: Emergency Care and Early Managementmentioning
confidence: 99%